Multidisciplinary Treatment of Deep Non‐Carious Cervical Lesion With a CAD/CAM Chairside Restoration in Combination With Periodontal Surgery: A 60‐Month Follow‐Up Technique Report. Issue 2 (23rd February 2021) - Durán, Juan C.; Alarcón, Carolina; De la Jara, Dolores; Pino, Rodrigo; Lanis, Alejandro
Abstract : Introduction: Restoring function and esthetics are essential aspects of periodontology and restorative dentistry. Depending on their extension and the tissues involved, the treatment of non‐carious cervical lesions (NCCLs) associated with gingival recessions may require a multidisciplinary approach, and different periodontal and restorative techniques have been described. Case Presentation: This case report presents an innovative approach to treat a deep NCCL combined with a gingival recession in a canine region of a female patient. A Computer Aided Design – Computer Aided Manufacturing (CAD/CAM) chairside ceramic restoration in combination with mucogingival surgery procedures is described. A comprehensive analysis of the selected approach and its clinical implications is presented based on a 60‐month follow‐up. Conclusions: After 60‐month follow‐up, clinical condition maintained stable, and a successful esthetic outcome was accomplished. Complete root coverage was achieved and kept throughout the whole period of tracing.